Experimental Investigation into Compressive Behaviour and Preconsolidation Pressure of Structured Loess at Different Moisture Contents - Yali Xu; Panpan Guo; Chengwei Zhu; Gang Lei; Kang Cheng (Geofluids)
This paper investigates the influence of the structured property of loess on its compressive behaviour and proposes a new method for determining the preconsolidation pressure of structured loess soil. A series of oedometer tests were carried out on undisturbed and remoulded loess samples prepared at various moisture contents. The effects of moisture content on the structured yield stress, the preconsolidation pressure, and the structural strength were also captured. It was found that the influence of the structured property of loess on the compression behaviour is divergent between undisturbed and remoulded loess samples. The discrepancy before and after structural yielding is more remarkable for the undisturbed soil. The Casagrande method realized through the MATLAB program can effectively eliminate human factors and accurately calculate the corresponding preconsolidation pressure for undisturbed soil. The effects of moisture content on the method for determining the preconsolidation pressure considering the structured property of loess were discussed. The determination method can accurately evaluate the loess consolidation state in loess regions. The influencing rules which the moisture content exerts on the structured yield stress, the preconsolidation pressure, and the structural strength all conform to exponential functions. The study is of great significance to correctly differentiating the foundation consolidation states and calculating the ground settlement in loess regions.